THE EFFECT OF PADI HUSK BIOCHAR COMBINATION AND CHICKEN MANURE AGAINST KALE GROWTH AND RESULTS (Brassica oleraceae var. Acephala L.) IN PEATLAND - Noni Sari, Kristina; Ruliyansyah, Agus; Zulfita, Dwi (Fakultas Pertanian Universitas Tanjungpura, 2019)
Kale plants are a type of green vegetables belonging to Brassica originating from the Eastern Mediterranean or Asia. Kale plants are also dubbed the